Byłaś moim niebem…, czyli o miłości, która nie umiera - Karkut, Dorota (Dydaktyka Polonistyczna, 2017)
In the review a book of Barbara Litwicka You were my heaven was discussed. Issues brought upby the author are providing readers with not only the entertainment and the relaxation, but above allprovoking reflection. They are determining the axiological and existential perspective, encouragingto empathic reading. This is one of the books which through the composition, genre and creations ofthe main characters open up various interpretative proposals, associations and discussions.